Design, Synthesis, Characterization, and Computational Studies on Benzamide Substituted Mannich Bases as Novel, Potential Antibacterial Agents - Suman Bala; Neha Sharma; Anu Kajal; Sunil Kamboj (The Scientific World Journal)
A series of benzamide substituted Mannich bases (1–7) were synthesized. The synthesized derivatives were authenticated by TLC, UV-Visible, FTIR, NMR, and mass spectroscopic techniques and further screened for in vitro antibacterial activity by test tube dilution method using amoxicillin and cefixime as standard drugs. The compounds 5, 6, and 7 were found to be the most active antibacterial agents among all the synthesized compounds. The physicochemical similarity of the compounds with standard drugs was assessed by calculating various physicochemical properties using software programs. The percent similarity of synthesized compounds was found to be good and compound 1 was found to have higher percentage of similarity. The compounds were subjected to QSAR by multilinear regression using Analyze it version 3.0 software, and four statistically sound models were developed with R2 (0.963–0.997), Radj2 (0.529–0.982), and Q2 (0.998–0.999) with good F (2.35–65.56) values.